A Benign Anomalous Umbilical Vein: Not All Umbilical Veins That Wander Are Lost. Issue 1 (March 2016) - Morgan, Tara A.; Salmeen, Kirsten; Filly, Roy A.
Abstract : Abstract: A rare case of an anomalous umbilical vein with a previously unreported outcome is described. Most reported cases of anomalous umbilical veins are associated with significant concurrent fetal anomalies and poor outcomes. Fetal magnetic resonance imaging was used in this case to confirm normal portal and hepatic venous vasculature. No other fetal anomalies were identified on ultrasound. The infant was delivered at term and is healthy at the age of 8 months. Parental anxiety regarding the diagnosis was the only adverse consequence of this incidental finding.